(untitled) (Journal of Economic Additions, 2026)
This study explores the strategic importance of adopting Agile practicies in project management, focusing on their essential role in accelerating product development and ensuring high quality. The research highlights how these practices support innovation and rapid response to change by fostering a culture of collaboration and mutual trust within self-organizing teams. Additionally, it examines the Spotify Model as a successful case study that drove company growth through enhanced organizational flexibility. The study concludes that the Spotify Agile model is not just a framework, but a pioneering structural and cultural vision to be emulated within specific context. Jel Classification Codes: M00, M10, M19